Konsep Pemikiran Mehdi Golshani Terhadap Sains Islam dan Modern - Fadlih Rifenta (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
During Islamic science development, Islamic community is divided into two groups. First, who is aimed to create rationalist society and being scientific in viewing the science by accepting it entirely from western view. Second, who decisively refuse the Western modernity by the argument that science and Islam can burgeon by turning back into Islamic foundations. Mehdi Golshani tries to explain the actual concept of Islamic science and criticism toward Western science. Based on result of this research, it can be concluded that first, Islamic science is the science which is based on Islamic values, such as the worldview in metaphysic form or Islamic philosophy assumption, epistemiologic principle and Islamic ethic in any science dimension. Second, criticism toward modern science is basically for positivism, secularism which is existent behind of epistemiology of modern science. Therefore, according to Mehdi Golshani the steps of scientific research which is done recently, ecpecially emphasizing on observastion and experiment is the standard step which is also done by Muslim scientist